Real-Time Simulation Modeling Method of Multiphase Converters Based on High-Order Approximation in Micro-grid - Hao, Xiaoliang; Fu, Lijun; Ma, Fan; Hu, Liangdeng; Zhang, Xueyan (Frontiers in Energy Research, 2022)
As more and more distributed energy resources accessing in a micro-grid, the electromagnetic transient simulation of the whole system becomes extremely complicated due to the increase of multiphase converters. The traditional real-time simulation models of multiphase converters are low in efficiency for their large number of electronic switches and power system nodes. To solve this problem, an efficient real-time simulation modeling method based on high-order approximation is proposed. Starting with the symmetry of structure, the twelve-phase converter and induction motor are equivalent to a three-phase converter and induction motor and thus reducing the order of the model. The switching function model of the three-phase converter is derived, and the mathematical expressions of switching functions are calculated by high-order approximation expansion of the Fourier series; then, the dc input current of the three-phase converter is formulated theoretically. Counteracting the harmonics by means of phase-shifting, the high-order approximation model of the twelve-phase converter is constructed. Finally, the real-time simulation platform and experimental platform of the twelve-phase frequency converter and induction motor are built; the simulation results verify the high efficiency and accuracy of the proposed real-time simulation model compared with traditional models of the multiphase frequency converter.